Spinorphin inhibits membrane depolarization- and capsaicin-induced intracellular calcium signals in rat primary nociceptive dorsal root ganglion neurons in culture. (2nd November 2015) - Ayar, Ahmet; Ozcan, Mete; Kuzgun, Kemal Tuğrul; Kalkan, Omer Faruk
Abstract: Objective : Spinorphin is a potential endogenous antinociceptive agent although the mechanism(s) of its analgesic effect remain unknown. We conducted this study to investigate, by considering intracellular calcium concentrations as a key signal for nociceptive transmission, the effects of spinorphin on cytoplasmic Ca 2+ ([Ca 2+ ]i ) transients, evoked by high-K + (30 mM) depolariasation or capsaicin, and to determine whether there were any differences in the effects of spinorphin among subpopulation of cultured rat dorsal root ganglion (DRG) neurons. Methods : DRG neurons were cultured on glass coverslips following enzymatic digestion and mechanical agitation, and loaded with the calcium sensitive dye fura-2 AM (1 µM). Intracellular calcium responses in individual DRG neurons were quantified using standard fura-2 based ratiometric calcium imaging technique. All data were analyzed by using unpaired t test, p  < 0.05 defining statistical significance. Results : Here we found that spinorphin inhibited cytoplasmic Ca 2+ ([Ca 2+ ]i ) transients, evoked by depolarization and capsaicin selectively in medium and small cultured rat DRG neurons. Spinorphin (10–300 µM) inhibited the Ca 2+ signals in concentration dependant manner in small- and medium diameter DRG neurons. Capsaicin produced [Ca 2+ ]i responses only in small - and medium - sized DRG neurons, and pre-treatment with spinorphin significantly attenuated these [Ca 2+ ]i responses. Conclusion : Results from this study indicates that spinorphin significantly inhibits [Ca 2+ ]i signaling, which are key for the modulation of cell membrane excitability and neurotransmitter release, preferably in nociceptive subtypes of this primary sensory neurons suggesting that peripheral site is involved in the pain modulating effect of this endogenous agent.